The Relationship Between Duration Of Gadget Playing And The Level Of Cognitive Development In School-Age Children At Sd Negeri 5 Blang Pidie, Aceh West South Distric) - Zakiyah; Anita Tiara (Science Midwifery, 2022)
Many children already have their own gadgets and use the internet through their gadgets, but these incidents can have both positive and negative impacts. The use of gadgets that are not limited to children will cause gadget addiction. This study uses a correlation analytic method with a cross sectional approach. This research was conducted at SD Negeri 5 Blang Pidie, Aceh Barat Daya District in February 2022. The population in this study was students from grades 4 to grade 6 at SD Negeri 5 Blang Pidie, Aceh Barat Daya District, totaling 90 people. Determination of the number of samples using total sampling technique. Data was collected using a questionnaire. Methods univariate data analysis using the frequency distribution and bivariate with the Chi-Square test. The results of the chi square test show that the duration of playing gaget is related to the level of cognitive development of school-age children (p value 0.000). The conclusion of this study is that there is a relationship between the duration of playing gadgets and the level of cognitive development of school-age children. It is suggested to parents to be able to supervise children playing gadgets.